1974
DOI: 10.2170/jjphysiol.24.649
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Cooling Contracture of Toad Cardiac Muscles

Abstract: Summary The effect of rapid cooling on the mechanical activities of the cardiac muscles of the Japanese toad was examined. 1. The mechanical responses produced by rapid cooling (230•Ž) in both auricular and ventricular muscle preparations were composed of an immediate effect (phasic contraction) and a delayed effect (tonic contraction). The immediate effect was blocked by TTX, but the delayed effect was not affected by TTX and Mn. 2. The tonic contraction of the delayed effect produced by rapid cooling was pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…2 A-D The present study showed that caffeine induced contracture in frog cardiac muscle after exposure to Ca-rich solution. Like the cooling contracture of SAKAI and KURIHARA (1974) and the contracture presented by other authors (FOZZARD, 1977), the contracture was composed of initial transient and late sustained tensions. The initial tension in caffeine contracture observed here was similar to that in ferret heart muscle reported by CHAPMAN and LEOTY (1976), in the manner that it was transient and was little dependent on Ca concentration during caffeine application.…”
mentioning
confidence: 68%
“…2 A-D The present study showed that caffeine induced contracture in frog cardiac muscle after exposure to Ca-rich solution. Like the cooling contracture of SAKAI and KURIHARA (1974) and the contracture presented by other authors (FOZZARD, 1977), the contracture was composed of initial transient and late sustained tensions. The initial tension in caffeine contracture observed here was similar to that in ferret heart muscle reported by CHAPMAN and LEOTY (1976), in the manner that it was transient and was little dependent on Ca concentration during caffeine application.…”
mentioning
confidence: 68%
“…of skeletal muscle fibres after treatment with a low concentration of caffeine (Kurihara et al 1984) further suggests that rapid cooling in cardiac muscle depends on Ca2+ release from the s.r. In amphibian cardiac muscles, rapid cooling initiates contracture in the presence of caffeine (Chapman & Ellis, 1974;Sakai & Kurihara, 1974). The fact that mammalian cardiac muscle has a different critical r.c.c.…”
Section: Intracellular Store Bitesmentioning
confidence: 99%
“…Caffeine contracture is readily induced in a sodium free medium (14,15). When RCCC was elicited in a Na-free medium (the NaCl was totally replaced by K2SO4 or choline chloride) containing 1.8 mM Ca2+, the mechanical responses produced by rapid cooling in both caffeinized (1 mM) cat and frog ventricle muscles were composed of an immediate effect (phasic contracture) and a delayed effect (tonic contracture) as reported by Sakai and Kurihara (16). In the Ca-deprived medium, only a tonic contracture was elicited by rapid cooling, as shown in the present experiments.…”
Section: Discussionmentioning
confidence: 59%
“…RCCC in frog skeletal muscles (15) and rapid cooling contracture without caffeine (RCC) in cardiac muscles (16) have been studied by Sakai who concluded that the contractile mechanism in RCCC or RCC must be due to the mobilization of bound Ca from SR (frog skeletal muscles and guinea pig cardiac muscles) or cell membrane (bufo cardiac muscles).…”
Section: Discussionmentioning
confidence: 99%